Zmiany polskiego prawa samorządowego w 1938 roku - Podkowski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article presents the most important changes in the Polish local government law introduced in 1938. They were the last major regulations in this respect before the outbreak of the Second World War. They resulted from regular legislative activities as well as experiences of previous years with applying such legal solutions. The regulations concerned the status of the cities of Gdynia and Warsaw; receivables of municipalities from the settlements of accounts with the owners of the abolished areas under landowners’ rule; elections to village, commune, city and district councils; as well as shortening of the term in office of some local government bodies.
Keywords: prawo samorządowe; samorząd terytorialny